Mechanistic Insights into the Pd-Catalyzed Carbonylation of Alkynol for $α$-Methylene-$β$-Lactone Formation (Communications in Computational Chemistry, 2025)
Density functional theory (DFT) calculationswere performed to elucidate the reaction mechanism of thePd-catalyzed carbonylation of propargylic alcohol (1),leading to the efficient synthesis of cyclohexyl $α$-methylene-$β$-lactone (2). Our study revealed that thereaction proceeds through a four-step pathway: alkynemigration and insertion, CO insertion, HCl-assistedhydrogen transfer, and final C–O annulation. Notably, thefinal C–O annulation step was identified as the rate-determining step (RDS) of the overall catalysis, with a free energy barrier of25.7 kcal/mol (i.e., $IM4→TS4).$ Additionally, we uncovered the critical role of the HCl during the reaction pathway, ademonstrating that it acts as a co-catalyst, proton shuttle, and hydrogen bond donor/acceptor. NBO, EDA-NOCV, and HIGManalyses further revealed that the remarkable stability of the transition state $TS3$ in the presence of HCl primarily arises fromstrong electrostatic attraction and orbital interaction energies between the two interacting fragments. These mechanistic insightsprovide valuable insight and guidance for the rational design of new Pd-catalyzed transformations.